ANALISIS PENGUATAN KINERJA PEGAWAI BKPSDM KABUPATEN PIDIE JAYA BERDASARKAN BUDAYA KERJA, PENGALAMAN KERJA DAN DISIPLIN KERJA - Maskur Maskur; Kamaruddin Kamaruddin (Fakultas Ekonomi Universitas Almuslim Bireuen, 2025)
Employee performance research or analysis is always interesting, and is still being carried out, besides there are still problems, organizations are also increasingly competitive. In this analysis, it is taken from the perspective of three factors, namely work culture, work experience and work discipline. With the object of research 48 employees in the BKPSDM office environment of Pidie Jaya district. Applying a quantitative associative method, with a collection instrument through a questionnaire. Analyzed statistically inferentially, namely path model analysis. The results of the study found: (1) that the three factors, namely work culture, experience and employee work discipline have a positive effect on their performance, both directly and indirectly, respectively by 52.44%, 50.18% and 35.32%. (2) there is a causal relationship between the selected exogenous variables with a moderate category, so that simultaneously work culture, work experience and work discipline contribute 65% in strengthening employee performance.